Investigation on properties of composite film using carboxymethylcellulose - Loh, Win Kei (2022)

(untitled)
Recently, researchers have been focusing on the development of sustainable packaging to minimize the environmental issues created by conventional packaging.In this study, Carboxymethylcellulose (CMC), is used as an organic matrix for the formation of biocomposite film, one of the potential sustainable packaging due to its good film-forming ability, biodegradable and low-cost. With this purpose, the biocomposite film was prepared with nanomer PGV as reinforcement inorganic filler to increase the stiffness and strength of a polymer matrix and PEG as plasticizermainly to improve the flexibility and the water vapor barrier properties of the biocomposite films. These all ingredients were mixed at various content (CMC) content: 1 g, 2 g and 3 g, PEG content: 0.5 g, 0.6 g and 0.7 g, PGV content: 0.1 g, 0.2 g and 0.3 g) to form homogeneous solution before the film is formed via a simple casting method. The properties of the film were then characterized with Fourier Transform Infrared Spectroscopy (FTIR) analysis, Thermogravimetric analysis (TGA), tensile test and water solubility test.